Widefield fluorescence lifetime imaging of protoporphyrin IX for fluorescence‐guided neurosurgery: An ex vivo feasibility study. Issue 6 (20th February 2019) - Erkkilä, Mikael T.; Bauer, Bianca; Hecker‐Denschlag, Nancy; Madera Medina, Maria J.; Leitgeb, Rainer A.; Unterhuber, Angelika; Gesperger, Johanna; Roetzer, Thomas; Hauger, Christoph; Drexler, Wolfgang; Widhalm, Georg; Andreana, Marco
Abstract : Achieving a maximal safe extent of resection during brain tumor surgery is the goal for improved patient prognosis. Fluorescence‐guided neurosurgery using 5‐aminolevulinic acid (5‐ALA) induced protoporphyrin IX has thereby become a valuable tool enabling a high frequency of complete resections and a prolonged progression‐free survival in glioblastoma patients. We present a widefield fluorescence lifetime imaging device with 250 mm working distance, working under similar conditions such as surgical microscopes based on a time‐of‐flight dual tap CMOS camera. In contrast to intensity‐based fluorescence imaging, our method is invariant to light scattering and absorption while being sensitive to the molecular composition of the tissue. We evaluate the feasibility of lifetime imaging of protoporphyrin IX using our system to analyze brain tumor phantoms and fresh 5‐ALA‐labeled human tissue samples. The results demonstrate the potential of our lifetime sensing device to go beyond the limitation of current intensity‐based fluorescence‐guided neurosurgery. Abstract : To optimize the resection of gliomas during neurosurgery, we present an imaging system capable of wide field fluorescence lifetime mapping with 11 mm field of view and 250 mm working distance. Based on a time of flight dual‐tap CMOS camera and a modulated laser at 405 nm, we show unobserved quenching effects in tissue phantoms and demonstrate lifetime imaging on 5‐aminolevulinic acid (5‐ALA) labeled human ex vivo brain tumor samples.